2022
DOI: 10.3390/md20080526
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive Cytochalasins from the Mangrove Endophytic Fungus Phomopsis asparagi DHS-48

Abstract: Three new cytochalasins, phomoparagins A-C (1–3), along with five known analogs (4–8), were isolated from Phomopsis asparagi DHS-48, a mangrove-derived endophytic fungus. Their structures, including their absolute configurations, were elucidated using a combination of detailed HRESIMS, NMR, and ECD techniques. Notably, 1 possessed an unprecedented 5/6/5/8/5-fused pentacyclic skeleton. These compounds were tested for their inhibitory activity against concanavalin A (ConA)/lipopolysaccharide (LPS)-induced spleen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…All the isolated metabolites were evaluated for their cytotoxic and immunosuppressive activities according to the previously described methods [ 46 , 47 , 48 ]. Compounds 1 – 9 showed broad cytotoxic activity ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the isolated metabolites were evaluated for their cytotoxic and immunosuppressive activities according to the previously described methods [ 46 , 47 , 48 ]. Compounds 1 – 9 showed broad cytotoxic activity ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In continuing the search for structurally novel and biologically active natural products from mangrove endophytic fungi [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], a strain of Phomopsis asparagi DHS-48 isolated from the fresh root of Rhizophora mangle was found to be particularly productive with regard to the accumulation of a series of immunosuppressive chromones and cytochalasins [ 46 , 47 , 48 ]. With the goal of tapping the metabolic potential of this titled fungal strain, we initiated the co-culture fermentation process of well-characterized DHS-48 with other fungal strains.…”
Section: Introductionmentioning
confidence: 99%
“…Previous feeding experiments with sodium 13 C-labeled acetate by Lösgen et al [ 56 ] in 2007 revealed that a heptaketide precursor is involved in the biosynthesis of 3 and 4 , which are analogues to phomochromenones D-G isolated in our previous study [ 46 ], implying some cryptic post-synthesis modification genes were stimulated by the currently adopted epigenetic manipulation for the production of those metabolites previously unobserved or merely increased sufficiently under epigenetic control to be detected. Cytochalasins 5–11 might rationally share a common biosynthetic precursor as we previously described via polyketide synthase (PKS)/nonribosomal peptide synthetase (NRPS) hybrid machinery [ 38 ]. The stimulated metabolite 5 was is likely to be also derived from 6 by epoxidation, meanwhile 9 feasibly converted through catalytic dehydration.…”
Section: Resultsmentioning
confidence: 99%
“…The coelomycetous genus Phomopsis belongs to the family Diaporthaceae and consists of approximately 900 fungal species from a wide range of hosts [ 29 ]. The different species belonging to the genus Phomopsis are especially known for producing a wide variety of compounds with pharmacological properties, notably cytotoxic [ 30 , 31 , 32 ], antimicrobial [ 33 , 34 , 35 ], β -site amyloid precursor protein cleaving enzyme 1 (BACE1) inhibitory [ 36 ], anti-Tobacco mosaic virus (TMV) [ 37 ] and immunosuppressive activities [ 38 ]. As part of our research on discovering structurally novel and biologically active natural products from mangrove-derived endophytic fungal strains [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], a strain of Phomopsis asparagi DHS-48 isolated from the fresh root of Rhizophora mangle attracted our attention for the characterization of a series of immunosuppressive chromones [ 46 ] and cytochalasins [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation